2021
DOI: 10.3390/molecules26071975
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorogenic Assay: Analysis of Chemical Modification of Lysine and Arginine to Control Proteolytic Activity of Trypsin

Abstract: The chemical modification of amino acids plays an important role in the modulation of proteins or peptides and has useful applications in the activation and stabilization of enzymes, chemical biology, shotgun proteomics, and the production of peptide-based drugs. Although chemoselective modification of amino acids such as lysine and arginine via the insertion of respective chemical moieties as citraconic anhydride and phenyl glyoxal is important for achieving desired application objectives and has been extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As a proof of concept, trypsin was chosen as the model protease which is a serine protease with high specificity for the carboxyl side of arginine (Arg) sites (Scheme 2). 29–31 The angiotensin (Ang) peptide, one type of bioactive peptide of the brain renin–angiotensin system, which displays an affinity for type 1 and type 2 Ang receptors to regulate blood pressure, 32,33 was chosen as the model peptide due to the existence of an Arg residue. Carboxylatopillar[6]arene (CP6A), a popular water-soluble pillararene derivative with good water solubility and excellent recognition properties was chosen as macrocyclic receptor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a proof of concept, trypsin was chosen as the model protease which is a serine protease with high specificity for the carboxyl side of arginine (Arg) sites (Scheme 2). 29–31 The angiotensin (Ang) peptide, one type of bioactive peptide of the brain renin–angiotensin system, which displays an affinity for type 1 and type 2 Ang receptors to regulate blood pressure, 32,33 was chosen as the model peptide due to the existence of an Arg residue. Carboxylatopillar[6]arene (CP6A), a popular water-soluble pillararene derivative with good water solubility and excellent recognition properties was chosen as macrocyclic receptor.…”
mentioning
confidence: 99%
“…Previous studies have shown that trypsin specifically cleaved peptide sequences on the carboxyl side of the Arg and Lys sites. 29–31 Free Ang III and Ang III/CP6A were incubated with trypsin. First, the calibration curves of Ang III were derived and used for calculating the Ang III concentration in the following stability experiment (Fig.…”
mentioning
confidence: 99%